INNOVATIVE CONCEPTS IN ELECTRICAL ENGINEERING EDUCATION - SERAFÍN, Čestmír (Trends in education, 2016)
This paper is a theoretical study in identifying paths to innovative processes in the electronics education. The paper discussed the latest trends in education including cooperative learning, inquirybased learning and constructivist approach. The paper outlines the changes in areas that set a barrier in the way of teaching in technical subjects, with an emphasis on electrical resting on the general perception that these subjects / courses are practical, useful and promising, but difficult and troublesome. This concept is needed by all participants in the educational process to overcome.
Keywords: Education; Electrical training; Innovation in teaching; Educational process; Subject didactics